PENINGKATAN KETRAMPILAN BERBICARA DAN PENILAIN MAHASISWA PRODI BAHASA INGGRIS MELALUI PENDEKATAN KOMUNIKATIF TIPE DEBAT AKADEMIS DAN PENJURIAN TEMAN SEKELAS - I Ketut Wardana (SPHOTA: Jurnal Linguistik dan Sastra, 2015)
Abstract Excellent English Speaking ability and assessment of oral production can be one of success indicators for students of English study program at Mahasaraswati Denpasar University to be qualified teachers. However, students of semester four G still found weaknesses to obtain. This present research was conducted to improve their learning achievement in speaking skill and assessment. It made use a classroom action research design through communicative approach type academic debate and oral production test. The initial condition of students speaking skill was categorized as poor level because the mean score of pretest was 50. The application of cyclic process, which consisted of two cycles, involved four steps: planning, action, observation and reflection. The increasing ability in each cycle could be seen from their scores either individual or team. The individual score of each session for three aspects of debate had gradually increased. The mean score of cycle I was 72 which can be categorized as sufficient level and cycle two was 83 which meant at very good level. The students’ responses were also positive after this learning model was applied. They also admitted that they had learned many things which were related to their skill in controlling emotion, practicing speaking ability, enriching vocabularies, and arguing in positive attitude. Based on the finding and discussion, the communicative approach type academic debate and oral production assessment can improve students’ ability in speaking English. Key words: academic debate, communicative, assessment